Place of death in rural palliative care: A systematic review. (September 2016) - Rainsford, Suzanne; MacLeod, Roderick D; Glasgow, Nicholas J
Background: There have been many studies on the actual and preferred place of care and death of palliative patients; however, most have been whole population surveys and/or urban focused. Data and preferences for terminally ill rural patients and their unofficial carers have not been systematically described. Aim: To describe the actual place of death and preferred place of care and/or death in rural palliative care settings. Method: A systematic mixed studies review using Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Data source: PubMed, PsychINFO, Scopus and CINAHL databases were searched (September to December 2014); eligible quantitative and qualitative studies included preferred and/or actual place of death/care of rural, regional or remote residents; rural data that are clearly identifiable; death due to palliative condition (malignant and non-malignant) or survey of participants with current or hypothetical life-limiting illness. Results: A total of 25 studies described actual place of death; 12 preferred place of care or death (2 studies reported both); most deaths occurred in hospital with home as the preferred place of care/death; however qualitative studies suggest that preferences are not absolute; factors associated with place are not adequately described as rurality was an independent variable; significant heterogeneity (rural setting and participants), however, many areas had a greater chance of home death than in cities; rural data are embedded in population reports rather than from specific rural studies. Conclusion: Home is the preferred place of rural death; however, more work is needed to explore influencing factors, absolute importance of preferences and experience of providing and receiving palliative care in rural hospitals which often function as substitute hospice.